Territorial hypothesis predicts the trade-off between reproductive opportunities and parental care in three species of damselfishes (Pomacentridae: Actinopterygii) - Bessa, Eduardo [UNESP] (2012)
Paternal care is rare in most animals, but common in fishes, including Pomacentridae. One way of explaining it is through the territorial hypothesis, which predicts that paternal care may evolve when caring for a territory with eggs will not cost more than territories without eggs. Here we describe the reproductive behavior of three pomacentrids from São Paulo, Brazil, and evaluate if the territorial hypothesis explains their behavioral variation through five predictions. We checked if females have multiple spawns (prediction 1), if they forage more (prediction 2) and if territory defence demands more when eggs are present (prediction 3). We also described how visible eggs are (prediction 4) and how available nesting sites are (prediction 5). Chromis multilineata differed from Abudefduf saxatilis and Stegastes fuscus by not guarding the eggs, spending less time with territoriality and fanning eggs; and more time feeding and foraging. Females of the three species are iteroparous. Females' A. saxatilis and S. fuscus foraged more than males, which spent the same amount of time in territorial defence before and after eggs were delivered. These two species also have very conspicuous egg clutches on clean rock surfaces defended by them. on the other hand, males and females of C. multilineata spent the same time foraging, while territoriality took more effort after eggs were present and it spawns cryptic eggs amid Sargassum, a common and disperse micro-environment in São Paulo rocky shores. Territorial hypothesis explains why paternal care by A. saxatilis and S. fuscus lasts longer than by C. multilineata.